Evaluation of Online-Based Services at The Population and Civil Registration Office of Tomohon City - Mandagi, Marthinus; Kairupan, Sisca; R. Palar, Frilia; Mantiri, Jeane; Onibala, Nancy (Iapa Proceedings Conference, 2024)
This research aims to analyse, describe and find out the evaluation of online-based services at the Tomohon City Population and Civil Registration Service. This research was carried out using qualitative research methods. The number of informants in this research was seven people. Data collection used observation, interview and documentation techniques. Data analysis through data reduction, data presentation and drawing conclusions. The results of this research show an evaluation of online-based services at the Tomohon City Population and Civil Registration Service using the E-dukcapil application which aims to make things easier for the community and can be used by all residents of Tomohon City. In the use of this application, there has been a decline in users of this online-based service, as will happen in 2022, where there will be a decline in the use of this online-based service. This occurs due to a lack of attention from officers to make more efforts to promote online-based services for the Tomohon E-dukcapil application and people who prefer manual services even though the existence of this service is to make it easier for people who do not need to directly process population documents at the office. Tomohon City DUKCAPIL Service. This is also related to the online-based service process carried out by employees at the DUKCAPIL Service, the services provided by existing employees and their implementation.